E-business process management - Nah, Fiona Fui-Hoon, 1966-; Rosemann, Michael, 1967-; Watson, Ed (Business process management journal, 2004)
Enterprise systems packages have long been associated with process change. However, it was assumed that most organizations would simultaneously design and implement process change while implementing the systems. A survey of 163 organizations and detailed interviews with 28 more suggests that enterprise systems were still being implemented even among early adopters of the technology, and that process change was being undertaken on an ongoing basis. After the prerequisites of time, critical mass of functionality, and significant expenditures were taken care of, the factors most associated with a.